1995
DOI: 10.1159/000168859
|View full text |Cite
|
Sign up to set email alerts
|

Carotid-Jugular Arteriovenous Fistula: A Complication of Temporary Hemodialysis Catheter

Abstract: The internal jugular vein is increasingly being used as a temporary route for dual-lumen hemodialysis catheter placement. It is thought to be safer than the subclavian or femoral vein sites. It is important, however, to point out that this route can also be associated with serious complications. Herein we describe a case of right common carotid artery fistula as a complication of the insertion of a polyurethane double-lumen hemodialysis catheter into the right internal jugular vein. A review of the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 28 publications
0
38
0
2
Order By: Relevance
“…Although it is a simple application in experienced hands it can be associated with many complications, one of which is carotid artery-IJV fistula, a rare complication that has been described in the literature [2,3]. Herein, we report a case with carotid artery-IJV fistula who presented with catheter dysfunction and interruption of HD treatment.…”
Section: Figmentioning
confidence: 98%
See 2 more Smart Citations
“…Although it is a simple application in experienced hands it can be associated with many complications, one of which is carotid artery-IJV fistula, a rare complication that has been described in the literature [2,3]. Herein, we report a case with carotid artery-IJV fistula who presented with catheter dysfunction and interruption of HD treatment.…”
Section: Figmentioning
confidence: 98%
“…IJV catheterization can be associated with many well-documented complications [4,5,6,7,8], but AVF between the carotid artery and IJV is rare [2,3,4]. In a minority of cases it develops from the carotid arterial puncture (CAP), and CAP is a frequent complication because of the anatomic relation of the two vessels with an incidence of 2–9.9% [9].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors include a table of reported cases of acquired carotid-jugular fistulas from 1994 up to 2000, which includes the observations of Gobeil et al (1994) [28], Al-Kutoubi and Kreel (1994) [29], El-Shahawy and Khilnani (1995) [30], Nandapelan et al (1995) [31], Chen et al (1995) [32], Nemzek et al (1996) [33], Huart et al (1996) [34], and Avrahami et al (1997) [35]. Two further cases from before 2000, not reported by Talwar, were seen in the Croatian War by Kaklikkaya et al (1999) [36] and Zakhariev et al (1999) [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The subclavian catheter carries a high incidence of venous stricture as well as life-threatening traumatic complications [4, 5, 6, 7, 8], while the femoral catheter is frequently associated with infective complications and phlebothrombosis [9]. However, numerous complications of internal jugular venous cannulation have been reported due to uncertainty about vascular locations [10, 11, 12, 13, 14]. …”
Section: Introductionmentioning
confidence: 99%